Romancing the stone [videorecording (DVD)] - Douglas, Michael, 1944-; Douglas, Michael, 1944-; Turner, Kathleen, 1954-; DeVito, Danny; Norman, Zack; Arau, Alfonso; Ojeda, Manuel R. (20th Century Fox Home Entertainment, 1999)
A romance writer sets off to Colombia to pay the ransom of her kidnapped sister, and soon finds herself in the middle of a dangerous adventure. Thrown into a jungle full of gunfire, mud slides and poisonous snakes, Joan's only hope lies with Jack Colton, a rugged wanderer straight out of her novels. Together, they'll have to outwit the bandits and survive the jungle if they're to save her sister.